Rhizofungus Aspergillus terreus Mitigates Heavy Metal Stress-Associated Damage in Triticum aestivum L. - Dilawar, Naveen; Hamayun, Muhammad; Iqbal, Amjad; Lee, Bokyung; Ali, Sajid; Ahmad, Ayaz; Alrefaei, Abdulwahed Fahad; Faraj, Turki Kh.; Kim, Ho-Youn; Hussain, Anwar (MDPI AG, 2024)
Industrial waste and sewage deposit heavy metals into the soil, where they can remain for long periods. Although there are several methods to manage heavy metals in agricultural soil, microorganisms present a promising and effective solution for their detoxification. We isolated a rhizofungus, Aspergillus terreus (GenBank Acc. No. KT310979.1), from Parthenium hysterophorus L., and investigated its growth-promoting and metal detoxification capabilities. The isolated fungus was evaluated for its ability to mitigate lead (25 and 75 ppm) and copper (100 and 200 ppm) toxicity in Triticum aestivum L. seedlings. The experiment utilized a completely randomized design with three replicates for each treatment. A. terreus successfully colonized the roots of wheat seedlings, even in the presence of heavy metals, and significantly enhanced plant growth. The isolate effectively alleviates lead and copper stress in wheat seedlings, as evidenced by increases in shoot length (142%), root length (98%), fresh weight (24%), dry weight (73%), protein content (31%), and sugar content (40%). It was observed that wheat seedlings possess a basic defense system against stress, but it was insufficient to support normal growth. Fungal inoculation strengthened the host's defense system and reduced its exposure to toxic heavy metals. In treated seedlings, exposure to heavy metals significantly upregulated MT1 gene expression, which aided in metal detoxification, enhanced antioxidant defenses, and maintained metal homeostasis. A reduction in metal exposure was observed in several areas, including normalizing the activities of antioxidant enzymes that had been elevated by up to 67% following exposure to Pb (75 mg/kg) and Cu (200 mg/kg). Heavy metal exposure elevated antioxidant levels but also increased ROS levels by 86%. However, with Aspergillus terreus colonization, ROS levels stayed within normal ranges. This decrease in ROS was associated with reduced malondialdehyde (MDA) levels, enhanced membrane stability, and restored root architecture. In conclusion, rhizofungal colonization improved metal tolerance in seedlings by decreasing metal uptake and increasing the levels of metal-binding metallothionein proteins.